OP0020 The Influence of Drug Exposures on Joint Surgeries in Rheumatoid Arthritis Patients: Cross-Provincial Comparisons. (9th June 2015) - Widdifield, J.; Moura, C.; Wang, Y.; Abrahamowicz, M.; Beauchamp, M.-E.; Paterson, M.; Huang, A.; Boire, G.; Fortin, P.; Bessette, L.; Bombardier, C.; Hanly, J.; et al.
Abstract : Background: Disease-modifying anti-rheumatic drugs (DMARDs) generally have the greatest impact if they are initiated early in the course of the disease. We hypothesized that greater cumulative exposure to DMARDs soon after RA diagnosis is associated with longer time to joint surgeries. Objectives: To evaluate early exposure to DMARDs and time to joint surgery, comparing incident rheumatoid arthritis (RA) populations from Ontario (ON) and Quebec (QC). Methods: Using a standard protocol, we performed population-based cohort analyses on new-onset RA patients in ON and QC from 2000-2013. Incident RA patients were followed from cohort entry until their first joint surgery, or were censored at death date, or the end of study period, whichever came first. We studied all recipients of public drug coverage, aged 66 years and older. Analyses were confined to "new users" for the drug of interest. We used Cox proportional hazards regression with time-dependent variables measuring duration of drug use (daily exposures in the first year of follow-up), separately for methotrexate and other DMARDs, adjusting for baseline age, sex, urban vs. rural residence, socioeconomic status, co-existing osteoarthritis (OA), comorbidities, prior joint surgeries, extra-articular RA manifestations, time-varying number of physician visits, and drug exposures (anti-TNF inhibitors, COXIBs, NSAIDs, systemic steroids). Adjusted hazard ratios (HRs) along with 95% confidence intervals (CIs), were estimated. Results: Among 20, 918 ON and 6, 740 QC RA patients, 68% were female and the mean (SD) age was 75 (6) years in each setting. During follow-up, 2, 201 (11%) in ON and 494 (7%) patients in QC underwent joint surgery, for a rate of 2 events per 100 person-years in both settings. In the multivariable analyses, greater exposure to methotrexate (HR 0.97 95%CI 0.95-0.98), and other DMARDs (HR 0.98 95%CI 0.97-0.99) within the first year was associated with longer time to surgery in both settings. The strongest independent associations with shorter time to surgery in ON and QC, respectively, included previous joint surgeries [HR=1.9 vs. 2.8], co-existing OA [HR=1.5 vs. 1.8], and greater exposure to NSAIDs [HR=1.2 vs. 1.3], and COXIBs [HR=1.1 vs. 1.3]. Conclusions: Greater cumulative exposures to methotrexate and other DMARDs, within 1 year after RA diagnosis, were associated with longer time to joint surgeries in both ON and QC. Our coordinated approach across provincial data sources identified highly comparable and consistent findings. Disclosure of Interest: None declared